CXCL10 and CCL21 promote migration of pancreatic cancer cells toward sensory neurons and neural remodeling in tumors in mice, associated with pain in patients - Hirth, Michael; Gandla, Jagadeesh; Höper, Christiane; Gaida, Matthias; Agarwal, Nitin; Simonetti, Manuela; Demir, Aykut; Xie, Yong; Weis, Cleo-Aron Thias; Michalski, Christoph; Hackert, Thilo; Ebert, Matthias; et al. (Gastroenterology, 2020)
Background & Aims - Pancreatic ductal adenocarcinoma (PDAC) is frequently accompanied by excruciating pain, which has been associated with attraction of cancer cells and their invasion of intrapancreatic sensory nerves. Neutralization of the chemokine CCL2 reduced cancer-associated pain in a clinical trial, but there have been no systematic analyses of the highly diverse chemokine families and their receptors in PDAC. - Methods - We performed an open, unbiased RNA-interference screen of mammalian chemokines in co-cultures of mouse PDAC cells (K8484) and mouse peripheral sensory neurons, and confirmed findings in studies of DT8082 PDAC cells. We studied the effects of chemokines on migration of PDAC cell lines. Orthotopic tumors were grown from K8484 cells in mice, and mice were given injections of neutralizing antibodies against chemokines, antagonists, or control antibodies. We analyzed abdominal mechanical hypersensitivity and collected tumors and analyzed them by histology and immunohistochemistry to assess neural remodeling. We collected PDAC samples and information on pain levels from 74 patients undergoing resection and measured levels of CXCR3 and CCR7 by immunohistochemistry and immunoblotting. - Results - Knockdown of 9 chemokines in DRG neurons significantly reduced migration of PDAC cells towards sensory neurons. Sensory neuron-derived CCL21 and CXCL10 promoted migration of PDAC cells via their receptors CCR7 and CXCR3, respectively, which were expressed by cells in orthotopic tumors and PDAC specimens from patients. Neutralization of CCL21 or CXCL10, or their receptors, in mice with orthotopic tumors significantly reduced nociceptive hypersensitivity and nerve fiber hypertrophy and improved behavioral parameters without affecting tumor infiltration by T cells or neutrophils. Increased levels of CXCR3 and CCR7 in human PDAC specimens were associated with increased frequency of cancer-associated pain, determined from patient questionnaires. - Conclusions - In an unbiased screen of chemokines, we identified CCL21 and CXCL10 as proteins that promote migration of pancreatic cancer cells toward sensory neurons. Inhibition of these chemokines or their receptors reduce hypersensitivity in mice with orthotopic tumors, and patients with PDACs with high levels of the chemokine receptors of CXCR3 and CCR7 had increased frequency of cancer-associated pain.
Gesehen am 24.09.2020